The effects of psychosocial factors on occupational accidents: a cross-sectional study in the manufacturing industry in Turkey - (:unkn) unknown (My University, 2021)
Objectives. Looking at death statistics in workplaces, occupational health and safety (OHS) is indisputably one of the most important problems of society. Considering that the existing measures are insufficient to reduce deaths, it is essential to look at the prevention of occupational accidents/diseases with an interdisciplinary approach and to employ new perspectives in order to develop new methods. The aim of this study is to determine whether psychosocial risks are perceived as an accident factor by employees and to bring the concept of psychosocial accident factors into a discussion. Methods. The survey technique is used as a data collection tool for this study. The questionnaire has 33 questions. SPSS version 25.0 was used to analyze the data. Results. The study showed that employees who had an accident perceived psychosocial factors as an important accident factor. Conclusions. Studies on causes of accidents at work are generally based on a single dimension, such as environmental conditions and/or faults of employees. There is almost no focus on the reasons for the misbehaviors of employees. Psychosocial factors are not taken into account or neglected, but results show that providing psychosocial support and/or psychological counseling services in workplaces may be effective in reducing accidents.
Keywords: stress; accident factors; occupational accident; occupational health and safety; psychosocial risk factors